MoO3 induces p-type surface conductivity by surface transfer doping in diamond - Xing, Kaijian; Xiang, Yang; Jiang, Ming; Creedon, Daniel L.; Akhgar, Golrokh; Yianni, Steve A.; Xiao, Haiyan; Ley, Lothar; Stacey, Alastair; McCallum, Jeffrey C.; Zhuiykov, Serge; Pakes, Christopher I.; et al. (Applied Surface Science, 2020)
Surface transfer doping of diamond using high electron affinity transition metal oxides (TMOs), such as MoO3, has emerged as a key enabling technology for the development of diamond-based surface two-dimensional (2D) electronics. However, the omission of a critical pre-annealing step in the device fabrication process to remove atmospheric adsorbates prior to TMO deposition, as seen in numerous studies, makes the role of TMOs ambiguous in light of air-induced surface conductivity, preventing a full understanding of the intrinsic surface transfer doping behavior of TMO-based surface acceptors. Here, using in-situ four-probe electrical measurements we explicitly show the insulating-to-conducting transition in diamond surface driven by MoO3 induced surface transfer doping. Variable-temperature Hall-effect measurements reveal weak temperature-dependence down to 250 mK, evidencing the 2D Fermi liquid nature of the resulting surface conducting channel on diamond. Using first-principles calculations, we confirm the interfacial charge exchange upon MoO3 adsorption leading to a degenerate hole conducting layer on diamond. This work provides significant insights into understanding the surface transfer doping of diamond induced by TMOs, and paves the way for the investigations of many interesting quantum transport properties in the resulting 2D hole conducting layer, such as phase-coherent magnetotransport, on diamond surface.
CRIS-Team Scopus Importer:2020-03-13
Keywords: 2DHG; Diamond; Molybdenum trioxide; Surface conductivity; Surface transfer doping